(untitled) (Journal of Parents and Teachers, 2026)
In Europe, there are millions of people living in poverty, including the illiterate, the long-term unemployed, and the homeless. To try to mitigate this, various educational policies are being proposed to prevent these situations, including raising awareness and adapting programmes to individual learning speeds.